High-intensity interval training improves interventricular synchrony and strain under hypoxic stress in sedentary males. (25th November 2020) - Huang, Y.C; Wang, J.S
Abstract: Background: Interventricular interactions in increased RV afterload such as hypoxia stress, which affects both synchrony and function in an in-series effect as well as a parallel effect arising from leftward septal shift. Improved myocardial contractility is a critical circulatory adaptation to exercise training, however, the types of exercise that can improve interventricular synchrony under hypoxic environment have not yet been established. Purpose: This study investigates how high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) influence on the interventricular synchrony in response to normobaric hypoxia in sedentary men. Methods: Fifty-four sedentary males were randomized to perform HIIT (3-minute intervals at 40% and 80% VO2peak, n=18), MICT (sustained 60% VO2peak, n=18) for 30 minutes/day, 5 days/week for 6 weeks and the control group (CTL, n=18). Synchrony measurements at apical 4-chamber view including (1) intra-delay, the difference in time to peak strain (TS) between segmental septal-to-lateral ventricular or atrial walls, and (2) inter-delay, the difference in TS between RV or RA free wall and LV or LA lateral wall. The data were acquired by 2-dimensional speckle tracking echocardiography at rest under hypoxic condition (12% FIO2, simulated an altitude of 4, 500 m) before and after the interventions. Results: HIIT had significantly elevated radial and longitudinal strains in both LA and LV (p<0.05). As the results showed, HIIT was superior than MICT in improvement of longitudinal intra-delay of LV; furthermore, only HIIT simultaneously ameliorated both radial and longitudinal synchrony at apex. Although the HIIT enhanced intraventricular synchrony in both motions, whereas the interventricular synchrony deteriorated at radial motion. In atrium synchrony, although both groups augmented the intra-LA synchrony, however, only HIIT reduced the inter-delay between LA and RA at the roof motion. LV end-systolic volume (ESV) significantly correlated with the longitudinal inter-delay of ventricle (r=−0.53, p<0.05), whereas the LV end-diastolic volume (EDV) correlated with the inter-delay of atrium in roof motion (r=0.40, p<0.05). Conclusion: We found differences between HIIT and MICT in segmental intra- and inter- synchrony. HIIT enhanced both ventricular or atrial synchrony, and further increased the EDV coupled with decreased ESV. These findings give new insight into cardiac adaptation to difference endurance training and the long-term impact of such changes warrants future study in cardiac diseases. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Science Council of Taiwan